Nilai-Nilai Pendidikan Islam dalam Novel Reach Your Dreams Karya Wirda Mansur - Nadia Sri Ramdani; Rini Rahman (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the values ​​of Islamic education for adolescents in the novel Reach Your Dreams by Wirda Mansur. This research is research with a qualitative approach with the concept of content analysis research. Based on the problem formulation, this research focuses on what are the values ​​of Islamic education for teenagers contained in the novel Reach Your Dreams by Wirda Mansur. In collecting data, the hermeneutic analysis method was used to research and examine the Reach Your Dreams novel, in order to obtain data to determine the values ​​of Islamic education for adolescents in the novel. The collected data are grouped and then described. The findings of the collected values ​​are grouped into three main themes, namely: i) the value of faith, ii) the value of worship, iii) the value of morality. The results of this study can be used as initial data for future researchers in examining different issues related to this problem as well as various other issues relevant to this context.